Repetitive Transcranial Magnetic Stimulation Improves Neurological Function and Promotes the Anti-inflammatory Polarization of Microglia in Ischemic Rats - Luo, Jing; Feng, Yuan; Li, Mingyue; Yin, Mingyu; Qin, Feng; Hu, Xiquan (Frontiers in Cellular Neuroscience, 2022)
Ischemic stroke (IS) is a severe neurological disease that is difficult to recovery. Previous studies have shown that repetitive transcranial magnetic stimulation (rTMS) is a promising therapeutic approach, while the exact therapy mechanisms of rTMS in improving neural functional recovery remains unclear. Furthermore, the inflammatory environment may influence the rehabilitation efficacy. Our study shows that long-term rTMS stimulation will significantly promote neurogenesis, inhibit apoptosis and control inflammation. rTMS inhibits the activation of transcription factors NF-κB and STAT6, and promotes the anti-inflammatory polarization of microglia. Obvious promotion of anti-inflammatory cytokines production is observed both in vitro and in vivo through rTMS stimulation on microglia. In addition, NSCs cultured in conditioned medium (CM) from microglia treated with rTMS showed downregulation of apoptosis and upregulation of neuronal differentiation. Over all, our results illustrate that rTMS can modulate microglia with anti-inflammatory polarization variation, promote neurogenesis and improve neural function recovery.